Personal strategies to mitigate the effects of air pollution exposure during sport and exercise: a narrative review and position statement by the Canadian Academy of Sport and Exercise Medicine and the Canadian Society for Exercise Physiology - Hung, A.; Koch, S.; Bougault, V.; Gee, C. M.; Bertuzzi, R.; Elmore, M.; McCluskey, P.; Hidalgo, L.; Garcia-Aymerich, J.; Koehle, M. S. (British Journal of Sports Medicine, 2023)
Air pollution is among the leading environmental threats to health around the world today, particularly in the context of sports and exercise. With the effects of air pollution, pollution episodes (eg, wildfire conflagrations) and climate change becoming increasingly apparent to the general population, so have their impacts on sport and exercise. As such, there has been growing interest in the sporting community (ie, athletes, coaches, and sports science and medicine team members) in practical personal-level actions to reduce the exposure to and risk of air pollution. Limited evidence suggests the following strategies may be employed: minimising all exposures by time and distance, monitoring air pollution conditions for locations of interest, limiting outdoor exercise, using acclimation protocols, wearing N95 face masks and using antioxidant supplementation. The overarching purpose of this position statement by the Canadian Academy of Sport and Exercise Medicine and the Canadian Society for Exercise Physiology is to detail the current state of evidence and provide recommendations on implementing these personal strategies in preventing and mitigating the adverse health and performance effects of air pollution exposure during exercise while recognising the limited evidence base.